Residential indoor air quality interventions through a social‐ecological systems lens: A systematic review. (15th April 2021) - Tsoulou, Ioanna; Senick, Jennifer; Mainelis, Gediminas; Kim, Sunyoung
Abstract: Indoor air quality (IAQ) is an important consideration for health and well‐being as people spend most of their time indoors. Multi‐disciplinary interest in IAQ is growing, resulting in more empirical research, especially in affordable housing settings, given disproportionate impacts on vulnerable populations. Conceptually, there is little coherency among these case studies; they traverse diverse spatial scales, indoor and outdoor environments, and populations, making it difficult to implement research findings in any given setting. We employ a social‐ecological systems (SES) framework to review and categorize existing interventions and other literature findings to elucidate relationships among spatially and otherwise diverse IAQ factors. This perspective is highly attentive to the role of agency, highlighting individual, household, and organizational behaviors and constraints in managing IAQ. When combined with scientific knowledge about the effectiveness of IAQ interventions, this approach favors actionable strategies for reducing the presence of indoor pollutants and personal exposures.